Preliminary study of Gd-EOB-DTPA contrast-enhanced magnetic resonance imaging for determining gross tumor volume in hepatocellular carcinoma radiotherapy - Meng, Kangning; Gong, Guanzhong; Wang, Ruozheng; Yin, Yong (Frontiers in Oncology, 2026)
PurposeThe aim of this study was to evaluate the feasibility of gadolinium ethoxybenzyl diethylenetriamine pentaacetic acid (Gd-EOB-DTPA) contrast-enhanced magnetic resonance imaging (CE-MRI) for determining the gross tumor volume (GTV) of hepatocellular carcinoma (HCC).MethodsA retrospective analysis was conducted on 12 patients diagnosed with HCC (18 lesions) who received radiotherapy and underwent magnetic resonance (MR) simulation. Six series images, including MR T1-weighted image (T1WI) and contrast-enhanced T1WI (CE-T1WI) at 15 s, 45 s, 75 s, 150 s, and >20 min after Gd-EOB-DTPA injection, were obtained, and the GTV was determined in the different temporal images. The differences in mean signal intensity (SI), SI contrast between the HCC and liver tissue, volume and shape of HCC GTV among different phases were compared.Results(1) The mean SI of liver tissue reached its peak enhancement at >20 min, showing a 140.90 ± 64.69% increase, compared with T1WI (p < 0.05). (2) Compared with CE-T1WI-20min, the mean SI of the HCC increased by -41.19~18.09% from T1WI, CE-T1WI-15s to CE-T1WI-150s. Conversely, the mean SI of liver tissue decreased by 5.27~55.87% over the same period. Consequently, the SI contrast between HCC and liver tissue decreased by 53.30~89.37%. (3) The maximum GTV volume determined by CE-T1WI-20min was (22.80 ± 18.57) cm3, coinciding with the highest value of SI contrast (0.29 ± 0.16). (4) Compared with GTV-20min, GTV-T1WI and GTV-15s~GTV-150s had volume reductions of 6.73~19.35%. (5) Compared with GTV-20min, the Dice similarity coefficients (DSC) of GTV-T1WI and GTV-15s~GTV-150s ranged from 0.745 to 0.819. Additionally, the shape change trend of GTV in the CE-T1WI images was generally consistent with the volume change trend.ConclusionCE-T1WI MR images acquired more than 20 min post-injection of Gd-EOB-DTPA exhibited significant advantages in determining the GTV boundaries and enhancing the contrast of SI between HCC and liver tissue. The CE-T1WI-20min sequence is recommended for determining HCC GTV.